Factors contributing toward sleep quality among primary school children in Batu Pahat, Johor, Malaysia - Juhari, Nur Amalin (2019)
Poor sleep quality in children leads to physical and mental health problems; it can be a prognostic indicator of emotion and behavioural problems in adolescence and adulthood. This cross-sectional study aimed to determine factors contributing toward sleep quality among primary school children (aged 7 to 11 years) in Batu Pahat district, Johor. The present study involved 627 pairs of children-parent from six randomly selected primary schools in Batu Pahat, Johor. The parents completed a set of questionnaire which contained information on socio-demographic characteristics, sleep quality, eating styles and food groups consumption of their children. Meanwhile, the children completed a set of questionnaire that assessed physical activity andmeal intakes frequency. Their body weight, height and waist circumference were measured by a trained researcher, and their BMI-for-age and central obesity were determined. Also, each child was interviewed on a one-to-one manner for their dietary intakes in the past 24 hours by a trained nutritionist. The present study found that the mean total sleep disorder score of children was 52.3 ± 7.8, with a poor sleep quality prevalence of 74.2%. Meanwhile, the average total sleep duration of children was almost 9 hours 22 minutes per day (8.9 ± 1.2 hours), and 74.3% of them had inadequate total hours of sleep. In bivariate analyses, parental education (father: r=-0.095, p<0.05; mother: r=- 0.136, p<0.05), monthly household income (r=-0.128, p<0.05), frequency of fruits group intake (r= -0.131, p<0.05), frequency of vegetables group intake (r=-0.133, p<0.05), frequency of milk and dairy milk products group intake (r=- 0.086, p<0.05), desire to drink (r=0.176, p<0.05), food responsiveness (r=0.245, p<0.05), emotional over-eating (r=0.267, p<0.05), satiety responsiveness (r=0.192, p<0.05), emotional under-eating (r=0.185, p<0.05), and slowness in eating (r=0.175, p<0.05) were significantly correlated with sleep quality of the children. Nevertheless, no significant results were found between age, sex, ethnicity, BMI-for-age, waist circumference, physical activity, macronutrient intakes, adequacy of fruit and vegetable intake, meal intake frequencies and sleep quality in bivariate analyses. Variables with p<0.25 in univariate regression analysis such as ethnicity, parental educations, monthly household income, physical activity, total energy intake (kcal), frequency intakes of vegetables, milk and dairy milk products, afternoon tea, and supper, enjoyment of food, desire to drink, food responsiveness, emotional overeating, satiety responsiveness, emotional undereating, and slowness in eating were included in multiple linear regression (MLR) model. By using stepwise method in MLR, the result showed that Indian ethnicity (β=3.858), low monthly household income (β=-3.213), high emotional over-eating (β=0.383), high food responsiveness (β=0.302), high satiety responsiveness (β=0.357), increased in slowness in eating (β=0.256), and less frequent vegetables group consumption (β=-1.579) contributed significantly toward poor sleep quality of the children. These significant factors explained 18.6% of the total variances in sleep quality of the children. Further, being emotional overeating was found to be as the most important contributor in poor sleep quality of the children, with the highest R2 changed (7.1%) as compared to other factors. In conclusion, a majority of children (74.2%) were having poor sleep quality. Being an Indian, with lower total household income, increased intake of food due to emotions, high responsiveness towards food, high responsiveness of feeling full, eating very slowly and less frequent intakes of vegetables were associated with poorer sleep quality in children. Hence, future health promotion programmes for children should consider improving sleep quality as one of the main health outcomes. The proposed programme should consider to promote healthy dietary practices in enhancing the sleep quality of children.